P519 Impact of skin examination prior to initiation of biological treatment in patients with Inflammatory Bowel Disease: preliminary data. (27th May 2021) - Hartl, C; Novacek, G; Reinisch, S; Saciri, A; Reinisch, W; Primas, C; Maier, H
Abstract: Background: Dermatological affections are common in patients with inflammatory bowel disease (IBD). We aimed to assess if skin examination prior to initiation of biologics in IBD patients would detect relevant skin diseases, such as skin malignancies, which could influence treatment as well as management. Methods: In this ongoing cohort study we included IBD patients of the Dept. of Gastroenterology and Hepatology of the Medical University of Vienna with indication for biological treatment. Consultants of Dermatology performed a complete dermatological screening prior to initiation of therapy. We recorded all pathological findings, although the focus of this study is on certain dermatoses of high impact (melanoma, non-melanoma skin cancer, hidradenitis suppurativa, pyoderma gangrenosum, erythema nodosum and warts). Furthermore, we used a detailed questionnaire comprised of family history, medication and personal history of IBD. In cases of diagnostic uncertainties we confirmed our differential diagnosis by histopathological and further diagnostic investigations. The descriptive results are given as absolute numbers and percentages. Results: 431 patients were included, 322 patients (74.7%) with Crohn's disease, 103 (23.9%) with ulcerative colitis and 6 (1.4%) with inflammatory bowel disease unclassified. Melanoma was diagnosed in 3 out of 431 patients (0.7%). Non-melanoma skin cancer was detected in 22 patients (5.2%). Pyoderma gangrenosum, hidradenitis suppurativa and erythema nodosum were present in 5 (1.2%), 12 (2.8%), and 3 (0.7%) patients, respectively. We found viral warts in 73 patients (16.9%). 88 patients (20.4%) received further diagnostic investigations and 302 patients (70.1%) dermatological treatment for the detected skin diseases. Conclusion: Dermatological screening prior to initiation of treatment with biologics can identify IBD patients with skin malignancies and other high-impact skin diseases. This may influence further IBD treatment as well as management decisions. We conclude that prior dermatological screening is of high importance for safe management of IBD patients with biological therapy.